2016
DOI: 10.1176/appi.ajp.2015.15020190
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal GABA Levels Measured With Magnetic Resonance Spectroscopy in Patients With Psychosis and Unaffected Siblings

Abstract: Objective:The authors sought to compare GABA levels in treated and untreated patients with psychosis with levels in their unaffected siblings and healthy control subjects, and to assess the effects of antipsychotic medications on GABA levels.Method: GABA+ levels (i.e., including signal from unrelated proteins or macromolecules) referenced to creatine or water were studied with J-edited proton spectroscopy in the dorsal anterior cingulate cortex of 289 individuals: 184 healthy control subjects, 83 treated patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 37 publications
1
32
2
Order By: Relevance
“…In the second study, which was conducted in drug-naive subjects at UHR for psychosis (17) and measured GABA levels in the MPFC and dorsal caudate, significant elevations compared to control subjects were found in both regions. However, there appears to be a regional specificity to the GABA elevations in unmedicated patients, since prior studies found no group differences in the dorsolateral prefrontal cortex (8), in the dorsal anterior cingulate cortex (12), or in the occipital cortex (15) despite having studied unmedicated patients. In addition, although at baseline in the present study we found elevated MPFC GABA levels in five non-responders compared to responders, suggesting that the elevations observed in unmedicated patients at baseline may be driven by the non-responders, this interpretation must be viewed as preliminary since it is based on a small sample size.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the second study, which was conducted in drug-naive subjects at UHR for psychosis (17) and measured GABA levels in the MPFC and dorsal caudate, significant elevations compared to control subjects were found in both regions. However, there appears to be a regional specificity to the GABA elevations in unmedicated patients, since prior studies found no group differences in the dorsolateral prefrontal cortex (8), in the dorsal anterior cingulate cortex (12), or in the occipital cortex (15) despite having studied unmedicated patients. In addition, although at baseline in the present study we found elevated MPFC GABA levels in five non-responders compared to responders, suggesting that the elevations observed in unmedicated patients at baseline may be driven by the non-responders, this interpretation must be viewed as preliminary since it is based on a small sample size.…”
Section: Discussionmentioning
confidence: 97%
“…GABAergic neurotransmission plays a critical role in the coordination of pyramidal cell activity, and its abnormalities have been linked to neurocognitive deficits in schizophrenia (5). Neuroimaging studies using proton magnetic resonance spectroscopy ( 1 H MRS) to measure GABA levels in vivo in schizophrenia have yielded variable results, with most studies in antipsychotic-treated, stable schizophrenia patients showing lower or normal GABA levels in the anterior cingulate cortex (6), the medial prefrontal cortex (MPFC) (711), the dorsolateral prefrontal cortex (8), the dorsal anterior cingulate cortex (9, 12), parieto-occipital cortices (7, 11, 13, 14), and the basal ganglia (7, 14) compared to healthy subjects, while studies in antipsychotic-free patients found lower GABA levels in the occipital cortex (15), normal levels in the dorsal anterior cingulate (12), or elevations in the ventromedial prefrontal cortex (16) and in the MPFC (8). Moreover, in the first study that measured GABA levels in both the MPFC and the dorsolateral prefrontal cortex of the same antipsychotic-free and antipsychotic-treated patients (8), GABA elevations were found in the MPFC of antipsychotic-free patients compared to both the medicated patients and control subjects, while no differences were found among the three groups in the dorsolateral prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in GABA concentrations in many mental illnesses can be very subtle . This places stringent requirements on the reproducibility of the GABA editing sequence.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred and thirty‐five healthy volunteers participated in Institutional Review Board‐approved protocols 95‐M‐0150 and 00‐M‐0085 between February 2008 and January 2015 . The volunteers were scanned on a 3‐T whole‐body scanner (GE, Milwaukee, WI, USA; 14 M4 platform) with a quadrature single‐channel transmit/receive radiofrequency (RF) coil (IGC Medical Advances, Milwaukee, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…MRS and, recently, 31P-MRS studies demonstrated the changes that happen in membrane phospholipid characteristics, pH, and bioenergetic status. Also, 1H-MRS can be applied to map local NAA variations and the treatment effects [159][160][161][162][163][164][165][166][167][168].…”
Section: Research Applicationsmentioning
confidence: 99%